Adverse Effects of Immunoglobulin Therapy - Guo, Yi; Tian, Xin; Wang, Xuefeng; Xiao, Zheng (Frontiers in Immunology, 2018)
Immunoglobulin has been widely used in a variety of diseases, including primary and secondary immunodeficiency diseases, neuromuscular diseases, and Kawasaki disease. Although a large number of clinical trials have demonstrated that immunoglobulin is effective and well tolerated, various adverse effects have been reported. The majority of these events, such as flushing, headache, malaise, fever, chills, fatigue and lethargy, are transient and mild. However, some rare side effects, including renal impairment, thrombosis, arrhythmia, aseptic meningitis, hemolytic anemia, and transfusion-related acute lung injury (TRALI), are serious. These adverse effects are associated with specific immunoglobulin preparations and individual differences. Performing an early assessment of risk factors, infusing at a slow rate, premedicating, and switching from intravenous immunoglobulin (IVIG) to subcutaneous immunoglobulin (SCIG) can minimize these adverse effects. Adverse effects are rarely disabling or fatal, treatment mainly involves supportive measures, and the majority of affected patients have a good prognosis.